The door in the wall - De Angeli, Marguerite 1889- (New York : Dell Publishing, 1949)
A crippled boy in fourteenth-century England proves his courage and earns recognition from the King.
Z
920
Z
Keywords: Middle Ages -- Fiction; People with disabilities -- Fiction